2020
DOI: 10.1002/ar.24503
|View full text |Cite
|
Sign up to set email alerts
|

Hiding in Plain Sight‐ancient Chinese anatomy

Abstract: For thousands of years, scientists have studied human anatomy by dissecting bodies. Our knowledge of their findings is limited, however, both by the subsequent loss of many of the oldest texts, and by a tendency toward a Eurocentric perspective in medicine. As a discipline, anatomy tends to be much more familiar with ancient Greek texts than with those from India, China, or Persia. Here, we show that the Mawangdui medical texts, entombed in the Mawangdui burial site in Changsha, China 168 BCE, are the oldest s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 10 publications
(15 reference statements)
0
13
0
Order By: Relevance
“…Parallel connections between anatomy, medicine, and spiritualism were drawn from the dissection of animals and the physical observation and examination of both living and dead human bodies, contributing to early texts in China (Loukas, Ferrauiola, Shoja, Tubbs, & Cohen‐Gadol, 2010; Shaw et al, 2020), India (Loukas et al, 2010; Rajgopal, Hoskeri, Bhuiyan, & Shyamkishore, 2002), and Greece (Ghosh, 2015; Marketos & Skiadas, 1999). In traditional Chinese medicine, for example, many descriptions of anatomy include a circulating vital life force, qi (Shaw et al, 2020), the harmonious dualism of yin and yang , and a delicate balance of the five elements (wood, fire, water, earth, and metal) or wu xing (Loukas, Ferrauiola, et al, 2010).…”
Section: The Origins Of Anatomy and Anatomical Dissectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parallel connections between anatomy, medicine, and spiritualism were drawn from the dissection of animals and the physical observation and examination of both living and dead human bodies, contributing to early texts in China (Loukas, Ferrauiola, Shoja, Tubbs, & Cohen‐Gadol, 2010; Shaw et al, 2020), India (Loukas et al, 2010; Rajgopal, Hoskeri, Bhuiyan, & Shyamkishore, 2002), and Greece (Ghosh, 2015; Marketos & Skiadas, 1999). In traditional Chinese medicine, for example, many descriptions of anatomy include a circulating vital life force, qi (Shaw et al, 2020), the harmonious dualism of yin and yang , and a delicate balance of the five elements (wood, fire, water, earth, and metal) or wu xing (Loukas, Ferrauiola, et al, 2010).…”
Section: The Origins Of Anatomy and Anatomical Dissectionmentioning
confidence: 99%
“…Records from ancient Persia indicate that the bodies of condemned criminals were used for dissection and medical research during the Achaemenian Dynasty (sixth to fourth centuries BCE) (Shoja & Tubbs, 2007). Shaw and colleagues argue that anatomical descriptions contained within the ancient Chinese Mawangdui medical texts (Figure 1), constituting an atlas written in the third century BCE but (unlike Herophilus's contemporaneous work) surviving to be discovered in 1973 CE, were also arrived at via systematic dissection (Shaw et al, 2020). In South Asia, where Ayurvedic tradition gave rise to a plenitude of medical and anatomical manuscripts written in Sanskrit (Wujastyk, 2008), there is evidence that human dissection may have begun in a limited setting at the same time or earlier.…”
Section: The Origins Of Anatomy and Anatomical Dissectionmentioning
confidence: 99%
“…In the arm, however, the presence of radial and ulnar arteries is a common pattern in most individuals, especially in the ancient time. So, the theory of Two Hand Yin Meridians was dominant in the early phase of Chinese medicine (Shaw, 2020).…”
Section: Figurementioning
confidence: 99%
“…The texts provided details on the original sites, distribution pathways, pathology, and related diseases of 11 meridians. A recent report suggested that the meridian pathways described in Mawangdui medical texts are earliest anatomical atlas equivalent to the lost Greek anatomy book (Shaw et al, 2020).…”
Section: Figurementioning
confidence: 99%
“…This is further supported by descriptions from the silk meridian books unearthed from Mawangdui Han Tomb (221‐168 BC). Among the 11 meridians initially described the two yin meridians in the forearm, namely Hand Shao Yin Meridian and Hand Tai Yin Meridian, correspond almost exactly with the paths of ulnar and radial arteries, respectively (Shaw et al, 2020). It was also stated in the silk books (Ma, 1980) that (1) pulses can be detected in yin meridians (no mention of yang meridians); (2) both hand yin meridians start from the heart and end at the wrists; (3) the pathology of hand yin meridians includes angina and necrosis of internal organs, and (4) patients suffering from acute illness of yin meridians (not yang meridians) may die quickly in days (heart attack?).…”
Section: Figurementioning
confidence: 99%